Attributes influencing young home buyer’s purchase decision / Farah Merican Isahak Merican...[et al.] - Isahak Merican, Farah Merican; Md Zani, Rosliza; Nazrin, Nizar; Mohd Zaki, Nabila
As the economy slows down, the researchers observe the slowing down of housing market transactions and residential construction activities. The market is indeed softer compared to the market few years ago and the current property market faces a new younger generations of buyers, thus giving the house developers a challenge in attracting buyers. In order to attract these niche buyers, house developers need to understand what appeal younger generations. The objective of this research is to identify the influencing attributes for young home buyers to consider when making a house purchase decision. This paper examines the impacts of alternative housing attribute preferences on housing purchase decisions. Focusing on housing intrinsic attribute, housing extrinsic attribute, environmental attribute, and location facilities and services, the research used the convenient-sampling method to reach its respondents. A total of 200 questionnaires were distributed to young potential buyers of a developer based in Guar Cempedak, Kedah. Based on 132 questionnaires returned, the results were analyzed using the reliability and regression analysis. The results showed that location facilities and services is the most dominant factor influencing young home buyers in their house purchase decisions.